Mathematics Achievement vs Parenting Style - Reni Untarti and Anggun Badu Kusuma (International Journal of Advanced Science and Technology, 2020)
The students’ characteristics determine the achievement to master mathematics, andthe parenting style determines the students’ character building. This research describedthe parenting style, which was related to the students’ mathematics achievement. Thisresearch belongs to descriptive qualitative research using 76 students of first-yearmathematics education as the subject of the study. The data were obtained from thequestionnaire, documentation, observation, and in-depth interview. The research showsthat the authoritative parenting style is the best style related to mathematics learningachievement. Besides, the authoritarian, although it can’t be better comparing withauthoritative, can develop the mathematics learning achievements as well. Permissivestyle is considered not to develop the students to get the achievement in mathematics andalso the rejecting-neglecting style too. However, the best achievement in mathematics isachieved by students with permissive parenting.